1999
DOI: 10.1136/gut.44.3.361
|View full text |Cite
|
Sign up to set email alerts
|

A blind comparison of the effectiveness of endoscopic ultrasonography and endoscopy in staging early gastric cancer

Abstract: Background/Aims-Endoscopic ultrasonography is expected to be useful for invasion depth staging of early gastric cancer. A prospective blind study of the staging characteristics of endoscopy and endoscopic ultrasonography for early gastric cancer was performed. Methods-Findings of endoscopy and endoscopic ultrasonography using a 20 MHz thin ultrasound probe were independently reviewed and the results of 52 early gastric cancer lesions analysed. Results-The overall accuracy rates in invasion depth staging of ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
90
2
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(100 citation statements)
references
References 24 publications
3
90
2
3
Order By: Relevance
“…However, even recent studies have reported widely varying diagnostic accuracies of 67-90 % when determining the depth of invasion using EUS, making it difficult to view the method as sufficiently reliable [9][10][11][12][13][14]. Furthermore, its diagnostic ability is similar to that of CE alone [15][16][17], and a number of studies have stated that EUS is unsuitable as a routine investigation for determining the depth of invasion by EGCs [15]. In recent years, there have been some promising reports regarding the determination of invasion depth using new modalities such as infrared endoscopy [18] and magnifying endoscopy with narrow-band imaging [19], but these are yet to produce consistently reliable results.…”
Section: Discussionmentioning
confidence: 98%
“…However, even recent studies have reported widely varying diagnostic accuracies of 67-90 % when determining the depth of invasion using EUS, making it difficult to view the method as sufficiently reliable [9][10][11][12][13][14]. Furthermore, its diagnostic ability is similar to that of CE alone [15][16][17], and a number of studies have stated that EUS is unsuitable as a routine investigation for determining the depth of invasion by EGCs [15]. In recent years, there have been some promising reports regarding the determination of invasion depth using new modalities such as infrared endoscopy [18] and magnifying endoscopy with narrow-band imaging [19], but these are yet to produce consistently reliable results.…”
Section: Discussionmentioning
confidence: 98%
“…The overall accuracy rates for determining depth of invasion of EGCs were between 63 and 73% by non-objective criteria [11,14,15]. Namieno et al [16] concluded that Tumor size (more than 30 mm) 2 0…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of high-frequency thin probes has allowed target scanning with high resolution under endoscopic control [8,9]. In spite of some excellent accuracy data [17], there have been no significant differences between EUS and endoscopy in terms of depth accuracy [14].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, EUS sometimes overestimates tumor depth [19] , leading to unnecessary surgery in some cases. Histological analysis of resected specimens provides the most accurate assessment of the tumor depth and lymphatic or venous involvement, which define requirement for surgery.…”
Section: Discussionmentioning
confidence: 99%